Motivasi Pekerja Ojek Konvensional dalam Era Transportasi Ojek Online (Studi pada Jasa Ojek Pangkalan di Jembatan Gurem Kabupaten Pamekasan) - Agung Widiyanto Santoso; Sarmini (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
Transportation is an important element in the life of the nation and state to facilitate community activities. Recently, a phenomenon has emerged where online motorcycle taxi transportation competes with the conventional motorcycle taxis that have existed for a long time. In this study, we will discuss the motivation of conventional motorcycle taxi workers in the era of online motorcycle taxi transportation at the base at the gurem bridge, Pamekasan city. The method in this study uses qualitative and the approach used is phenomenology. The theory that will be used in this research is social solidarity which is very suitable for this research because after the researcher got data from the sources in Bangkalan ojek, the gurem bridge, the researcher got data that these ojek workers were motivated because of their lack of understanding of technology (Gaptek), both are income that is considered more than online motorcycle taxis, the third is the solidarity between motorcycle taxi workers who are very close and the last is a comfortable, safe and calm work environment like family.